Effectiveness of Vibrapep (OPEP) on Pulmonary functions in phase one of cardiac rehabilitation-A Randomized controlled trial - Gaonkar, Aishwarya; Naik, Varun Chandrakant (Nepalese Heart Journal, 2024)
Background and Aims: According to the WHO report 2022, coronary artery disease is the most prevalent cardiac disease worldwide. Impaired respiratory muscle function, increased secretions and reduced vital capacity are pulmonary complications commonly associated with CABG and Valve replacement surgeries. The purpose of this study was to compare the effect of Vibrapep and standard phase one of cardiac rehabilitation exercises on pulmonary functions.Methods: A Randomized Controlled Trial was conducted on 46 participants. Participants were randomly allocated into two groups, Vibrapep and phase one of cardiac exercises were given to Group A (n = 23), while Group B (n = 23) received only phase one cardiac rehabilitation exercises. The intervention was administered for twice a day for 5 days. Outcome measures such as Sputum volume, maximal inspiratory and expiratory pressure, thoracic expansion, SPO2 level, blood pressure and Peak expiratory flow rate were evaluated at baseline and on 5th day of the study.Results: Wilcoxon test of within-group analysis revealed statistically significant improvements in all parameters for both the interventional and control groups (p